Innovative strategies for wastewater treatment: harnessing green technologies for sustainable resource recovery. a review - Al-Rajhi, Aisha M. H.; Abdelghany, Tarek M. (Frontiers in Environmental Science, 2025)
A major global issue that negatively affects both ecosystems and human populations alike is the inability to supply enough fresh water to fulfill demand. A gap among the supply and demand of water is its defining feature, and it can show itself as either a monetary or physical water shortage. Wastewater treatment plays a vital role in protecting the environment by eliminating contaminants that damage aquatic ecosystems, such as insufficient nutrients that lead to algal blooms, and for safeguarding human health by stopping the spread of pathogens that cause disease. The treatment of wastewater includes conventional physical, chemical, and biological techniques like activated sludge and sedimentation; nanotechnology that uses high-surface-area nanomaterials for adsorption and decomposition; and biotechnological techniques that use microorganisms in systems like oxidation ponds and trickling filters. Biotechnology offers sustainable biological routes to break degrade organic matter, nanotechnology offers sophisticated techniques for eliminating a variety of contaminants, and conventional approaches give a basis. This review highlights the conventional, biotechnological, and nanotechnology-based approaches used in wastewater treatment and discusses the key challenges and future directions in this critical field.